The Influence of Audit Tenure, Emotional Quotient, Time Budget Pressure and Professional Skepticism on Audit Quality at Public Accounting Firms in Jambi, Palembang and Pekanbaru - Sitorus, Paula Agustina; Kusumastuti, Ratih; Rahayu, Rahayu (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to analyze the effect of audit tenure, emotional quotient, time budget pressure, and professional skepticism on audit quality at public accounting firms (KAP) in Jambi, Palembang, and Pekanbaru Regions. This study uses primary data by distributing questionnaires to auditors who work at 12 (twelve) KAP Jambi, Palembang, and Pekanbaru. The sampling technique used was purposive sampling technique. This study used a sample of 54 respondents. The data analysis technique used in this research is multiple linear regression analysis using the SPSS version 29 program. The results showed that audit tenure, emotional quotient, time budget pressure, and professional skepticism simultaneously affect audit quality. Partially that audit tenure, time budget pressure, skepticism have an effect on audit quality, emotional quotient has no effect on audit quality.